1983
DOI: 10.1002/art.1780260703
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and specificity of antibodies to types I, II, III, IV, and V collagen in rheumatoid arthritis and other rheumatic diseases as measured by 125i‐radioimmunoassay

Abstract: Antibodies to human native and denatured types I, 11, 111, IV, and V collagens were measured using Iz5I-radioimmunoassay. Mean levels of binding by sera from 30 rheumatoid arthritis patients were significantly higher than those from 20 normal subjects against all of the collagens tested. The relative antibody concentration was higher in synovial fluid than in simultaneously obtained serum. Many patients with gout or various other rheumatic diseases also had detectable anticollagen antibodies. With a few notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
0
2

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 30 publications
(11 reference statements)
4
65
0
2
Order By: Relevance
“…Since Steffen and Timpl (1) showed, in 1963, that the antibodies to homogenates of joint capsule cartilage from RA patients were reactive with collagen, many studies have confirmed that sera from patients with RA have antibodies to a variety of collagens (1)(2)(3)(4)(5)(6)(7)(8)(9). When tested, these antibodies have been found at higher titer in patients' synovial fluid as well (9-1 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since Steffen and Timpl (1) showed, in 1963, that the antibodies to homogenates of joint capsule cartilage from RA patients were reactive with collagen, many studies have confirmed that sera from patients with RA have antibodies to a variety of collagens (1)(2)(3)(4)(5)(6)(7)(8)(9). When tested, these antibodies have been found at higher titer in patients' synovial fluid as well (9-1 1).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies have been demonstrated to react to some degree with all types of collagen tested (9), but major interest has centered on type I collagen, which is found predominantly in skin, bone, vessels, and at joint surfaces, and type I1 collagen, which is found in hyaline cartilage. Antibodies have been shown to react with native collagens (M), denatured collagens (2), or both native and denatured collagens (3,8,9,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations